Natural outpost to Britain's defences : a study of the Irish Treaty Ports 1914-1945 - Evans, David George Benjamin (Trinity College (Dublin, Ireland). Department of History, 2013)
The thesis is a general profile of the ports in the period from the beginning ot the First World War to the end of the Second World War, under a number of headings, but it retains the ports as the central topic. The seven years before and after they became known as the Treaty Ports are included because one objective of the thesis is to gain an understanding of why Britain attached such importance to them; believed them to be an integral part of the defence of the empire; and why they became the focus of Irish political objectives in the later 1930s.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin